2012
DOI: 10.1371/journal.pone.0049163
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Definitions for Intention-To-Treat in Relation to Missing Outcome Data: Systematic Review of the Methods Literature

Abstract: BackgroundAuthors of randomized trial reports seem to hold a variety of views regarding the relationship between missing outcome data (MOD) and intention to treat (ITT). The objectives of this study were to systematically investigate how authors of methodology articles define ITT in the presence of MOD, how they recommend handling MOD under ITT, and to make a proposal for potential improvement in the definition and use of ITT in relation to MOD.Methods and FindingsWe systematically searched MEDLINE in February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 14 publications
2
89
1
2
Order By: Relevance
“…in many cases (60%-75%), the analysis can also be influenced by missing observations and the way the missing data are treated. 66 Despite the fact that most rCts on antihypertensive therapy are intended to test the efficacy of a given medication, the attempt to achieve the therapeutic goal is done almost invariably through various combinations of the initially studied medications with other drugs given afterward. in this context, the intention-to-treat analysis would not express the efficacy of the drug to which the patient has been initially randomized, but the efficacy of the variable combination and interaction of the initial with subsequent drugs.…”
Section: Limitations Of Analysis Of Results Of Rctsmentioning
confidence: 99%
“…in many cases (60%-75%), the analysis can also be influenced by missing observations and the way the missing data are treated. 66 Despite the fact that most rCts on antihypertensive therapy are intended to test the efficacy of a given medication, the attempt to achieve the therapeutic goal is done almost invariably through various combinations of the initially studied medications with other drugs given afterward. in this context, the intention-to-treat analysis would not express the efficacy of the drug to which the patient has been initially randomized, but the efficacy of the variable combination and interaction of the initial with subsequent drugs.…”
Section: Limitations Of Analysis Of Results Of Rctsmentioning
confidence: 99%
“…The primary outcome variable (average healthiness of ready meals and pizzas purchased in T-1, T1 and T2) included MOD if the participant did not purchase any own brand ready meals or pizzas using their loyalty card in any of the three study phases. A systematic review of methods used to cope with MOD in intention-to-treat analyses demonstrated that there is no consensus towards a preferred approach, with arguments for restricting to complete case analysis and for imputation of missing data [32]. For the FLICC study we dealt with MOD in the sales data by employing imputation techniques (multiple imputation for the primary outcome variable and single imputation for the secondary outcome variables).…”
Section: Discussionmentioning
confidence: 99%
“…23 In ITT analysis all the participants in a trial are analyzed according to the intervention to which they were allocated, irrespectively of whether they received it or not. 19,21,23 ITT is desirable because it increases statistical power and precision, it preserves the aims of randomization and hence, it minimizes selection bias and confounding.…”
Section: Missing Not At Random (Mnar)mentioning
confidence: 99%
“…23 In ITT analysis all the participants in a trial are analyzed according to the intervention to which they were allocated, irrespectively of whether they received it or not. 19,21,23 ITT is desirable because it increases statistical power and precision, it preserves the aims of randomization and hence, it minimizes selection bias and confounding. 19,21,23 Moreover, ITT is favoured in the assessment of effectiveness (especially in pragmatic trials) as it mirrors the noncompliance and treatment changes that are likely to occur when the intervention is used in practice.…”
Section: Missing Not At Random (Mnar)mentioning
confidence: 99%
See 1 more Smart Citation